Reduced somatostatin signalling leads to hypersecretion of glucagon in mice fed a high-fat diet - Kellard, J; Rorsman, N; Hill, T; van der Bunt, M; Armour, S; Rorsman, P; Knudsen, J; Briant, L (Elsevier, 2020)
Objectives: Elevated plasma glucagon is an early symptom of diabetes, occurring in subjects with impaired glucose regulation. Here, we explored alpha-cell function in female mice fed a high-fat diet (HFD)—a widely used mouse model of prediabetes. Methods: We fed female mice expressing the Ca2+ indicator GCaMP3 specifically in alpha-cells an HFD or control (CTL) diet. We then conducted in vivo phenotyping of these mice, as well as experiments on isolated (ex vivo) islets and in the in situ perfused pancreas. Results: In vivo, HFD-fed mice exhibited increased fed plasma glucagon levels and a reduced response to elevations in plasma glucose. Glucagon secretion from isolated islets and in the perfused mouse pancreas was elevated under both hypo- and hyperglycaemic conditions. In mice fed a CTL diet, increasing glucose reduced intracellular Ca2+ ([Ca2+]i) (oscillation frequency and amplitude). This effect was also observed in HFD mice; however, both the frequency and amplitude of the [Ca2+]i oscillations were higher than those in CTL alpha-cells. Given that alpha-cells are under strong paracrine control from neighbouring somatostatin-secreting delta-cells, we hypothesised that this elevation of alpha-cell output was due to a lack of somatostatin (SST) secretion. Indeed, SST secretion in isolated islets from HFD mice was reduced but exogenous SST also failed to suppress glucagon secretion and [Ca2+]i activity from HFD alpha-cells, in contrast to observations in CTL mice. Conclusions: These findings suggest that reduced delta-cell function, combined with intrinsic changes in alpha-cell sensitivity to somatostatin, accounts for the hyperglucagonaemia in mice fed an HFD.